Far field prediction of radiated emission from pcb using near-field measurement - Loo, Shin Yi. (2010)
This report presents a new near field to far field transformation by using a statistical model approach that has yet to be introduced in the EMC community. The report begins with the introduction of near field to far field transformation which includes the background, motivation, objectives and scope of the project.